Water-in-salt redox hydrogel electrolyte as well as preparation method and application thereof
By using water-in-safe redox hydrogel electrolyte and carbon cloth electrode in flexible supercapacitors, the low electrochemical stability and operating voltage limiting of hydrogel electrolytes are solved, and the flexibility of high energy density and wide potential windows are achieved Supercapacitors have broadened their application areas.
Patent Information
- Application Number
- CN202411469796.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
AI Technical Summary
The existing flexible supercapacitors have limited energy storage capacity due to the low electrochemical stability of hydrogel electrolytes and the low operating voltage, making it difficult to broaden their application areas.
Water-in-safe redox hydrogel electrolyte is used to create a flexible supercapacitor by introducing aqueous salt solution and redox active substances into the electrolyte to broaden the working voltage of the hydrogel and improve its electrochemical performance.
The flexible supercapacitor has high energy density, power density and wide potential windows, which improves its electrochemical performance and stability, and is suitable for bending and other applications.
Smart Images

Figure HDA0005094379700000011 
Figure HDA0005094379700000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitors, and in particular to a water-in-salt redox hydrogel electrolyte and a preparation method and application thereof. Background Art
[0002] Flexible supercapacitors have the advantages of high power density, fast charge and discharge speed, long life stability, excellent flexibility and plasticity, etc. They can be flexibly integrated into various electronic devices, such as wearable devices, smart clothing and flexible displays, etc., and are one of the important directions for the development of energy storage in the future. Hydrogel electrolytes have become an ideal choice for the preparation of flexible supercapacitors due to their high conductivity, low cost and environmental friendliness. However, the electrochemical stability of hydrogel electrolytes is relatively low, and their thermodynamic voltage limit is 1.23V, which means that flexible supercapacitors can often only operate within an operating voltage range of about 1.0V. The lower operating voltage limits the energy storage capacity of supercapacitors, resulting in relatively low energy density. The development of hydrogel electrolytes with high voltage windows and high electrochemical properties is of great significance for improving the performance of supercapacitors and broadening their application areas.
[0003] A salt-in-water solution is a superconcentrated aqueous electrolyte in which the volume or weight ratio of salt to water is greater than 1. In a salt-in-water electrolyte, almost all water molecules form a strong coordination with the ions in the solvent sheath structure, which effectively inhibits the decomposition of water and gives it a high potential window comparable to that of non-aqueous electrolytes. Secondly, by introducing redox active substances into the electrolyte, their rapid and reversible redox reactions at the electrode / electrolyte interface during charging and discharging can bring additional Faraday pseudocapacitance, thereby further improving the electrochemical performance of the supercapacitor. Therefore, if the above two methods can be combined to prepare a salt-in-water redox hydrogel electrolyte, it is expected to provide a high voltage window and high capacitance for supercapacitors, thereby preparing flexible supercapacitors with both high energy density and high power density. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a salt-in-water redox hydrogel electrolyte and a preparation method and application thereof. By introducing a salt-in-water solution, the working voltage of the hydrogel can be widened; by introducing redox active substances, the electrochemical properties of the hydrogel can be improved.
[0005] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] In the first aspect, the present invention proposes a salt-in-water redox hydrogel electrolyte, the key of which is that the electrolyte consists of a polymer matrix, a salt solute, a redox active substance and a solvent, wherein the polymer matrix is one of polyvinyl alcohol or polyvinyl alcohol / polyacrylamide; the salt solute is zinc chloride; the redox active substance is one of ammonium ferrous sulfate, potassium bromide, zinc bromide, zinc iodide and potassium iodide; and the solvent is water.
[0007] Furthermore, the mass ratio of the polymer matrix to the salt solute in the electrolyte is (1-3):(5-15).
[0008] Furthermore, the concentration of the salt solute in the electrolyte is 7.5 to 10 mol kg -1 .
[0009] Furthermore, the concentrations of ammonium ferrous sulfate, potassium bromide, zinc bromide, zinc iodide or potassium iodide in the electrolyte are 0.05 to 0.3 mol kg -1 , 0.1~3mol kg -1 , 0.1~3mol kg -1 , 0.1~3mol kg -1 , 0.1~3mol kg -1 .
[0010] Furthermore, the concentration of potassium bromide in the electrolyte is 0.5 to 1 mol kg -1 .
[0011] In a second aspect, the present invention provides a method for preparing the water-in-salt redox hydrogel electrolyte according to the first aspect, comprising the following steps:
[0012] Step 1: Weigh a certain amount of zinc chloride and dissolve it in water to obtain a zinc chloride concentration of 7.5-10 molkg -1 of a saline-water solution;
[0013] Step 2, weighing a certain amount of redox active material and dissolving it in a salt-in-water solution to prepare a redox salt-in-water solution;
[0014] The redox active substance is ammonium ferrous sulfate, potassium bromide, zinc bromide, zinc iodide or potassium iodide, and the concentration of the redox active substance in the prepared redox salt-water solution is 0.05-0.3 mol kg -1 , 0.1~3mol kg -1 , 0.1~3molkg -1 , 0.1~3mol kg -1 or 0.1~3mol kg -1 ;
[0015] Step 3, adding the polymer matrix to the redox salt solution in a mass ratio of (1-3) to the salt solute of (5-15), heating in a water bath with stirring until the polymer matrix is completely dissolved;
[0016] Step 4: Cool naturally to room temperature and place to obtain a water-in-salt redox hydrogel electrolyte.
[0017] Furthermore, in step 3, the water bath heating temperature is 60 to 100° C., and the stirring time is 1 to 3 hours.
[0018] In a third aspect, the present invention provides another method for preparing the water-in-salt redox hydrogel electrolyte according to the first aspect, comprising the following steps:
[0019] Step 1: Weigh a certain amount of zinc chloride and dissolve it in water to obtain a zinc chloride concentration of 7.5-10 molkg -1 of saline-water solution;
[0020] Step 2: Weigh a certain amount of potassium bromide and dissolve it in the salt-water solution to obtain a potassium bromide concentration of 0.5-1 molkg -1 A redox salt-containing aqueous solution;
[0021] Step 3, adding 0.2 to 1 parts by weight of polyvinyl alcohol to the redox salt solution, heating in a water bath and stirring until the polymer matrix is completely dissolved, taking out and cooling to room temperature;
[0022] Step 4: add 1 to 7 parts by weight of acrylamide, 0.01 to 0.1 parts by weight of ammonium persulfate and 0.003 to 0.01 parts by weight of N,N-methylenebisacrylamide to the solution obtained in step 3 in sequence, dissolve completely, heat, and take out after polymerization reaction to obtain a water-in-salt redox hydrogel electrolyte.
[0023] Furthermore, in step 3, the heating temperature of the hot water bath is 60-100° C., and the stirring time is 1-3 hours; in step 4, the solution is placed in an oven at 50-100° C. for polymerization for 1-5 hours.
[0024] In a fourth aspect, the present invention further proposes an application of a water-in-salt redox hydrogel electrolyte in the preparation of a flexible supercapacitor, wherein the flexible supercapacitor comprises an electrode and a water-in-salt redox hydrogel electrolyte.
[0025] In a fifth aspect, the present invention provides a method for preparing the flexible supercapacitor, the steps of which are as follows:
[0026] The salt-in-water redox hydrogel electrolyte prepared in the second and third aspects is combined with a carbon cloth electrode to assemble into a flexible supercapacitor.
[0027] The remarkable effects of the present invention are:
[0028] 1. The present invention combines the advantages of water-in-salt hydrogel electrolytes and redox hydrogel electrolytes by adding different redox active substances to different water-in-salt hydrogel electrolytes, and can broaden the working voltage of the hydrogel electrolyte (up to 0-2V). The flexible supercapacitor constructed by the redox water-in-salt hydrogel electrolyte has high energy density and power density and is easy to operate.
[0029] 2. The flexible supercapacitor constructed by the present invention by combining carbon cloth electrodes and salt-in-water redox hydrogel electrolyte has a wide potential window and high capacitance, which is of great significance for the development of high energy density flexible supercapacitors.
[0030] 3. In the preparation methods of the two salt-in-water redox hydrogel electrolytes proposed in the present invention:
[0031] The preparation method described in the second aspect is simple and efficient, and the electrolyte is suitable for the casting process, so that the contact between the constructed flexible supercapacitor electrode and the electrolyte is more firm, thereby being more stable in applications such as bending;
[0032] The method described in the third aspect is to introduce the polyacrylamide polymer in the form of monomer acrylamide and perform in-situ polymerization. This method can accommodate a higher concentration of electrolyte. At the same time, this process makes the electrolyte preparation more controllable and easier to shape. The stability of the gel in different environments after shaping is also significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The cyclic voltammetry curves (a) of the flexible supercapacitor constructed in Example 1 of the present invention at different scan rates and the charge-discharge curves (b) at different current densities.
[0034] Figure 2 The flexible supercapacitors constructed by Examples 2, 3, 4, 5, and 6 of the present invention are -1 Cyclic voltammetry curves at scan rate (a) and 0.4 mA cm -2 Comparison of charge and discharge curves under current density (b). DETAILED DESCRIPTION
[0035] The specific implementation manner and working principle of the present invention are further described in detail below with reference to the accompanying drawings.
[0036] Comparative Example:
[0037] In this comparative example, the water-in-salt hydrogel electrolyte was prepared using the prior art, and the steps were as follows:
[0038] Step 1: Weigh 9.8 g of zinc chloride and dissolve it in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of saline-water solution;
[0039] Step 2, add 1.5 g of polyvinyl alcohol to the salt-packed aqueous solution, and stir at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol is completely dissolved;
[0040] Step 3: Cool naturally to room temperature to obtain a water-in-salt hydrogel electrolyte.
[0041] The prepared water-in-salt hydrogel electrolyte is used to assemble a flexible supercapacitor, and the steps are as follows:
[0042] A. Preparation of carbon cloth electrode:
[0043] The carbon cloth was soaked in 3MKOH solution for 1 h, taken out and calcined in a tube furnace at 500 °C for 1 h, with a heating rate of 5 °C min -1 ; Soak in 10 vol% HCl and deionized water for 5 min respectively, dry in an oven at 60°C for 1 h to obtain a carbon cloth electrode.
[0044] B. Construction of flexible supercapacitors:
[0045] The water-in-salt hydrogel electrolyte prepared in the comparative example and the carbon cloth electrode prepared in step A are assembled into a flexible supercapacitor.
[0046] Finally, the electrochemical performance of the flexible supercapacitor with salt-in-water hydrogel as electrolyte was tested by using a dual-electrode test system, cyclic voltammetry test and charge-discharge test at different scan rates or current densities. The test found that the constructed flexible supercapacitor system had a wide potential window of 0-1V and a charge-discharge rate of 0.4 mA cm -2 The maximum specific capacitance can reach 0.2mF cm at the current density -2 .
[0047] Embodiment 1:
[0048] This embodiment proposes a method for preparing a water-in-salt redox hydrogel electrolyte, and the specific steps are as follows:
[0049] Step 1: Weigh 9.8 g of zinc chloride and dissolve it in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of saline-water solution;
[0050] Step 2: Weigh 0.157 g of ammonium ferrous sulfate hexahydrate and stir to dissolve it completely in the salt-in-water solution to obtain a solution with a concentration of 0.05 mol / kg -1 A redox salt-containing aqueous solution;
[0051] Step 3, add 1.5 g of polyvinyl alcohol to the redox salt solution, and stir at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol is completely dissolved;
[0052] Step 4: Cool naturally to room temperature and place to obtain a water-in-salt redox hydrogel electrolyte.
[0053] The prepared salt-in-water redox hydrogel electrolyte is used to assemble a flexible supercapacitor, and the steps are as follows:
[0054] A. Preparation of carbon cloth electrode:
[0055] The carbon cloth was soaked in 3MKOH solution for 1 h, taken out and calcined in a tube furnace at 500 °C for 1 h, with a heating rate of 5 °C min -1 ; Soak in 10 vol% HCl and deionized water for 5 min respectively, dry in an oven at 60°C for 1 h to obtain a carbon cloth electrode.
[0056] B. Construction of flexible supercapacitors:
[0057] The water-in-salt redox hydrogel electrolyte prepared in Example 1 and the carbon cloth electrode prepared in step A are assembled into a flexible supercapacitor.
[0058] Finally, the electrochemical performance of the flexible supercapacitor with salt-in-water redox hydrogel as electrolyte was tested by using a dual-electrode test system, cyclic voltammetry test and charge-discharge test at different scan rates or current densities. The test found that the constructed flexible supercapacitor system had a wide potential window of 0-2V and a current of 0.4mAcm -2 The maximum specific capacitance can reach 1.4mF cm at the current density -2 , its energy density and power density are significantly higher than those of the control example.
[0059] Embodiment 2:
[0060] This embodiment proposes a method for preparing a water-in-salt redox hydrogel electrolyte, and the specific steps are as follows:
[0061] Step 1: Weigh 9.8 g of zinc chloride and dissolve it in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of saline-water solution;
[0062] Step 2: Weigh 0.476 g of potassium bromide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 0.5 mol / kg -1 A redox salt-containing aqueous solution;
[0063] Step 3, add 1.5 g of polyvinyl alcohol to the redox salt solution, and stir at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol is completely dissolved;
[0064] Step 4: Cool naturally to room temperature and place to obtain a water-in-salt redox hydrogel electrolyte.
[0065] The prepared salt-in-water redox hydrogel electrolyte is used to assemble a flexible supercapacitor, and the steps are as follows:
[0066] A. Preparation of carbon cloth electrode:
[0067] The carbon cloth was soaked in 3MKOH solution for 1 h, taken out and calcined in a tube furnace at 500 °C for 1 h, with a heating rate of 5 °C min -1 ; Soak in 10 vol% HCl and deionized water for 5 min respectively, dry in an oven at 60°C for 1 h to obtain a carbon cloth electrode.
[0068] B. Construction of flexible supercapacitors:
[0069] The water-in-salt redox hydrogel electrolyte prepared in Example 2 and the carbon cloth electrode prepared in step A are assembled into a flexible supercapacitor.
[0070] Finally, the electrochemical performance of the flexible supercapacitor with salt-in-water redox hydrogel as electrolyte was tested by cyclic voltammetry and charge-discharge test at different scan rates or current densities using a dual-electrode test system. The test found that the constructed flexible supercapacitor system had a wide potential window of 0-1.6V and a high current density of 0.4mA cm -2 The maximum specific capacitance can reach 0.38mF cm at the current density -2 , its energy density and power density are significantly higher than those of the control example.
[0071] Embodiment 3:
[0072] This embodiment proposes a method for preparing a water-in-salt redox hydrogel electrolyte, and the specific steps are as follows:
[0073] Step 1: Weigh 9.8g of zinc chloride and dissolve it in 8g of solvent water to obtain a zinc chloride concentration of 9molkg -1 of saline-water solution;
[0074] Step 2: Weigh 1.8 g of zinc bromide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 1 mol kg -1 A redox salt-containing aqueous solution;
[0075] Step 3, add 1.5 g of polyvinyl alcohol to the redox salt solution, and stir at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol is completely dissolved;
[0076] Step 4: Cool naturally to room temperature and place to obtain a water-in-salt redox hydrogel electrolyte.
[0077] The prepared salt-in-water redox hydrogel electrolyte is used to assemble a flexible supercapacitor, and the steps are as follows:
[0078] A. Preparation of carbon cloth electrode:
[0079] The carbon cloth was soaked in 3MKOH solution for 1 h, taken out and calcined in a tube furnace at 500 °C for 1 h, with a heating rate of 5 °C min -1 ; Soak in 10 vol% HCl and deionized water for 5 min respectively, dry in an oven at 60°C for 1 h to obtain a carbon cloth electrode.
[0080] B. Construction of flexible supercapacitors:
[0081] The water-in-salt redox hydrogel electrolyte prepared in Example 3 and the carbon cloth electrode prepared in step A are assembled into a flexible supercapacitor.
[0082] Finally, the electrochemical performance of the flexible supercapacitor with salt-in-water redox hydrogel as electrolyte was tested by cyclic voltammetry and charge-discharge test at different scan rates or current densities using a dual-electrode test system. The test found that the constructed flexible supercapacitor system had a wide potential window of 0-1.6V and a high current density of 0.4mA cm -2 The maximum specific capacitance can reach 0.21mF cm at the current density -2 , its energy density and power density are significantly higher than those of the control example.
[0083] Embodiment 4:
[0084] This embodiment proposes a method for preparing a water-in-salt redox hydrogel electrolyte, and the specific steps are as follows:
[0085] Step 1: Weigh 9.8g of zinc chloride and dissolve it in 8g of solvent water to obtain a zinc chloride concentration of 9molkg -1 of a saline-water solution;
[0086] Step 2: Weigh 2.56 g of zinc iodide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 1 mol kg -1 A redox salt-containing aqueous solution;
[0087] Step 3, add 1.5 g of polyvinyl alcohol to the redox salt solution, and stir at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol is completely dissolved;
[0088] Step 4: Cool naturally to room temperature and place to obtain a water-in-salt redox hydrogel electrolyte.
[0089] The prepared salt-in-water redox hydrogel electrolyte is used to assemble a flexible supercapacitor, and the steps are as follows:
[0090] A. Preparation of carbon cloth electrode:
[0091] The carbon cloth was soaked in 3MKOH solution for 1 h, taken out and calcined in a tube furnace at 500 °C for 1 h, with a heating rate of 5 °C min -1 ; Soak in 10 vol% HCl and deionized water for 5 min respectively, dry in an oven at 60°C for 1 h to obtain a carbon cloth electrode.
[0092] B. Construction of flexible supercapacitors:
[0093] The water-in-salt redox hydrogel electrolyte prepared in Example 4 and the carbon cloth electrode prepared in step A are assembled into a flexible supercapacitor.
[0094] Finally, the electrochemical performance of the flexible supercapacitor with salt-in-water redox hydrogel as electrolyte was tested by cyclic voltammetry and charge-discharge test at different scan rates or current densities using a dual-electrode test system. The test found that the constructed flexible supercapacitor system had a wide potential window of 0-1.2 V and a current density of 0.4 mA cm -2 The maximum specific capacitance can reach 0.27mF cm at the current density -2 , its energy density and power density are significantly higher than those of the control example.
[0095] Embodiment 5:
[0096] This embodiment proposes a method for preparing a water-in-salt redox hydrogel electrolyte, and the specific steps are as follows:
[0097] Step 1: Weigh 9.8g of zinc chloride and dissolve it in 8g of solvent water to obtain a zinc chloride concentration of 9molkg -1 of saline-water solution;
[0098] Step 2: Weigh 1.33 g of potassium iodide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 1 mol kg -1 A redox salt-containing aqueous solution;
[0099] Step 3, add 1.5 g of polyvinyl alcohol to the redox salt solution, and stir at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol is completely dissolved;
[0100] Step 4: Cool naturally to room temperature and place to obtain a water-in-salt redox hydrogel electrolyte.
[0101] The prepared salt-in-water redox hydrogel electrolyte is used to assemble a flexible supercapacitor, and the steps are as follows:
[0102] A. Preparation of carbon cloth electrode:
[0103] The carbon cloth was soaked in 3MKOH solution for 1 h, taken out and calcined in a tube furnace at 500 °C for 1 h, with a heating rate of 5 °C min -1 ; Soak in 10 vol% HCl and deionized water for 5 min respectively, dry in an oven at 60°C for 1 h to obtain a carbon cloth electrode.
[0104] B. Construction of flexible supercapacitors:
[0105] The water-in-salt redox hydrogel electrolyte prepared in Example 5 and the carbon cloth electrode prepared in step A are assembled into a flexible supercapacitor.
[0106] Finally, the electrochemical performance of the flexible supercapacitor with salt-in-water redox hydrogel as electrolyte was tested by using a dual-electrode test system, cyclic voltammetry test and charge-discharge test at different scan rates or current densities. The test found that the constructed flexible supercapacitor system had a wide potential window of 0-1V and a high current density of 0.4mA cm -2 The maximum specific capacitance can reach 0.33mF cm at the current density -2 , its energy density and power density are significantly higher than those of the control example.
[0107] Embodiment 6:
[0108] This embodiment proposes a method for preparing a water-in-salt redox hydrogel electrolyte, and the specific steps are as follows:
[0109] Step 1: Weigh 13.63 g of zinc chloride and dissolve it in 10 g of solvent water to obtain a zinc chloride concentration of 10 mol kg -1 of saline-water solution;
[0110] Step 2: Weigh 0.6 g of potassium bromide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 0.5 mol / kg -1 A redox salt-containing aqueous solution;
[0111] Step 3, adding 0.3 g of polyvinyl alcohol to the redox salt solution, stirring at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol is completely dissolved, and then cooling the gel to room temperature;
[0112] Step 4: 2.2 g acrylamide, 0.02 g ammonium persulfate and 0.0073 g N,N-methylenebisacrylamide were added successively and dissolved completely. The mixture was polymerized in an oven at 60° C. for 3 h and then taken out to obtain a water-in-salt redox hydrogel electrolyte.
[0113] The prepared salt-in-water redox hydrogel electrolyte is used to assemble a flexible supercapacitor, and the steps are as follows:
[0114] A. Preparation of carbon cloth electrode:
[0115] The carbon cloth was soaked in 3MKOH solution for 1 h, taken out and calcined in a tube furnace at 500 °C for 1 h, with a heating rate of 5 °C min -1 ; Soak in 10 vol% HCl and deionized water for 5 min respectively, dry in an oven at 60°C for 1 h to obtain a carbon cloth electrode.
[0116] B. Construction of flexible supercapacitors:
[0117] The water-in-salt redox hydrogel electrolyte prepared in Example 6 and the carbon cloth electrode prepared in step A are assembled into a flexible supercapacitor.
[0118] Finally, the electrochemical performance of the flexible supercapacitor with salt-in-water redox hydrogel as electrolyte was tested by using a dual-electrode test system, cyclic voltammetry test and charge-discharge test at different scan rates or current densities. The test found that in the wide potential window test of 0-1.6V for the constructed flexible supercapacitor system, 0.4mA cm -2 The maximum specific capacitance can reach 0.28mF cm at the current density -2 , its energy density and power density are significantly higher than those of the control example.
[0119] Embodiment 7:
[0120] The difference between this embodiment and embodiment 1 is that:
[0121] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of a saline-water solution;
[0122] In step 2, 0.314 g of ammonium ferrous sulfate hexahydrate was weighed to prepare a solution with a concentration of 0.1 mol kg -1 A redox salt-containing aqueous solution;
[0123] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0124] Embodiment 8:
[0125] The difference between this embodiment and embodiment 2 is that:
[0126] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of a saline-water solution;
[0127] In step 2, weigh 0.095 g of potassium bromide to prepare a solution with a concentration of 0.1 mol kg -1 A redox salt-containing aqueous solution;
[0128] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0129] Embodiment 9:
[0130] The difference between this embodiment and embodiment 3 is that:
[0131] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of a saline-water solution;
[0132] In step 2, weigh 0.18 g of zinc bromide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 0.1 mol / kg -1 A redox salt-containing aqueous solution;
[0133] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0134] Embodiment 10:
[0135] The difference between this embodiment and embodiment 4 is that:
[0136] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of a saline-water solution;
[0137] In step 2, weigh 0.256 g of zinc iodide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 0.1 mol kg -1 A redox salt-containing aqueous solution;
[0138] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0139] Embodiment 11:
[0140] The difference between this embodiment and embodiment 5 is that:
[0141] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of a saline-water solution;
[0142] In step 2, weigh 0.133 g of potassium iodide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 0.1 mol kg -1A redox salt-containing aqueous solution;
[0143] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0144] Embodiment 12:
[0145] The difference between this embodiment and embodiment 6 is that:
[0146] In step 1, 13.63 g of zinc chloride was weighed and dissolved in 10 g of solvent water to obtain a zinc chloride concentration of 10 mol kg -1 of saline-water solution;
[0147] In step 2, weigh 0.84 g of potassium bromide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 0.7 mol kg -1 A redox salt-containing aqueous solution;
[0148] In step 3, 0.3 g of polyvinyl alcohol was added to the redox salt solution, and the solution was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved, and then the gel was cooled to room temperature;
[0149] In step 4, 0.02 g of ammonium persulfate and 0.0073 g of N,N-methylenebisacrylamide were added to 2.2 g of acrylamide, and the mixture was polymerized in an oven at 60° C. for 3 h and then taken out to obtain a water-in-salt redox hydrogel electrolyte.
[0150] Embodiment 13:
[0151] The difference between this embodiment and embodiment 1 is that:
[0152] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of saline-water solution;
[0153] In step 2, 0.942 g of ammonium ferrous sulfate hexahydrate was weighed to prepare a solution with a concentration of 0.3 mol kg -1 A redox salt-containing aqueous solution;
[0154] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at a water bath temperature of 100° C. for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0155] Embodiment 14:
[0156] The difference between this embodiment and embodiment 2 is that:
[0157] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of a saline-water solution;
[0158] In step 2, weigh 2.856 g of potassium bromide to prepare a solution with a concentration of 3 mol kg -1 A redox salt-containing aqueous solution;
[0159] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0160] Embodiment 15:
[0161] The difference between this embodiment and embodiment 3 is that:
[0162] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of a saline-water solution;
[0163] In step 2, weigh 5.4 g of zinc bromide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 3 mol / kg -1 A redox salt-containing aqueous solution;
[0164] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0165] Embodiment 16:
[0166] The difference between this embodiment and embodiment 4 is that:
[0167] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of a saline-water solution;
[0168] In step 2, weigh 7.68 g of zinc iodide and stir to dissolve it completely in the salt-in-water solution to obtain a solution with a concentration of 3 mol / kg -1 A redox salt-containing aqueous solution;
[0169] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0170] Embodiment 17:
[0171] The difference between this embodiment and embodiment 5 is that:
[0172] In step 1, 9.8 g of zinc chloride was weighed and dissolved in 8 g of solvent water to obtain a zinc chloride concentration of 9 mol kg -1 of a saline-water solution;
[0173] In step 2, weigh 3.99 g of potassium iodide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 3 mol / kg -1 A redox salt-containing aqueous solution;
[0174] In step 3, 1.5 g of polyvinyl alcohol was added to the redox salt aqueous solution, and the mixture was stirred at 90° C. in a water bath for 2.5 h until the polyvinyl alcohol was completely dissolved.
[0175] Embodiment 18:
[0176] The difference between this embodiment and embodiment 6 is that:
[0177] In step 1, 13.63 g of zinc chloride was weighed and dissolved in 10 g of solvent water to obtain a zinc chloride concentration of 10 mol kg -1 of a saline-water solution;
[0178] In step 2, weigh 1.2 g of potassium bromide and stir to dissolve it completely in the salt-in-water solution to obtain a concentration of 1 mol / kg -1 A redox salt-containing aqueous solution;
[0179] In step 3, 0.3 g of polyvinyl alcohol is added to the redox salt solution, and the solution is stirred at 90° C. in a water bath for 3 h until the polyvinyl alcohol is completely dissolved.
[0180] In step 4, 0.02 g of ammonium persulfate and 0.0073 g of N,N-methylenebisacrylamide were added to 2.2 g of acrylamide, and the mixture was polymerized in an oven at 60° C. for 3 h and then taken out to obtain a water-in-salt redox hydrogel electrolyte.
[0181] Flexible supercapacitors were assembled using the salt-in-water redox hydrogel electrolytes prepared in Examples 7 to 18. A dual-electrode test system was then used to test the electrochemical properties of flexible supercapacitors using salt-in-water redox hydrogels as electrolytes at different scan rates or current densities using cyclic voltammetry and charge-discharge tests. The test found that the electrochemical properties of the flexible supercapacitors corresponding to Example 7 and Example 13 were basically the same as those of Example 1, the electrochemical properties of the flexible supercapacitors corresponding to Example 8 and Example 14 were basically the same as those of Example 2, the electrochemical properties of the flexible supercapacitors corresponding to Example 9 and Example 15 were basically the same as those of Example 3, the electrochemical properties of the flexible supercapacitors corresponding to Example 10 and Example 16 were basically the same as those of Example 4, the electrochemical properties of the flexible supercapacitors corresponding to Example 11 and Example 17 were basically the same as those of Example 5, and the electrochemical properties of the flexible supercapacitors corresponding to Example 12 and Example 18 were basically the same as those of Example 6.
[0182] In summary, the embodiments of the present invention effectively broaden the working voltage of the hydrogel electrolyte and improve the electrochemical properties of the hydrogel electrolyte by adding different redox active substances to different water-in-salt hydrogel electrolytes. At the same time, due to the combination of the advantages of the water-in-salt hydrogel electrolyte and the redox hydrogel electrolyte, the hydrogel electrolyte has a high potential window and high electrochemical properties. The flexible supercapacitor constructed using the redox water-in-salt hydrogel electrolyte and the carbon cloth electrode has a high energy density, power density and a working voltage of up to 0-2V, which is of great significance for the development of high energy density flexible supercapacitors.
[0183] The technical solution provided by the present invention is described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A water-in-salt redox hydrogel electrolyte, characterized in that: The electrolyte consists of a polymer matrix, a salt solute, a redox active substance and a solvent, wherein the polymer matrix is one of polyvinyl alcohol or polyvinyl alcohol / polyacrylamide; the salt solute is zinc chloride; the redox active substance is one of ammonium ferrous sulfate, potassium bromide, zinc bromide, zinc iodide and potassium iodide; and the solvent is water.
2. The water-in-salt redox hydrogel electrolyte according to claim 1, characterized in that: The mass ratio of the polymer matrix to the salt solute in the electrolyte is (1-3):(5-15).
3. The water-in-salt redox hydrogel electrolyte according to claim 1, characterized in that: The concentration of the salt solute in the electrolyte is 7.5 to 10 mol kg -1 .
4. The water-in-salt redox hydrogel electrolyte according to claim 1, characterized in that: The concentrations of ammonium ferrous sulfate, potassium bromide, zinc bromide, zinc iodide or potassium iodide in the electrolyte are 0.05 to 0.3 mol kg -1 , 0.1~3molkg -1 , 0.1~3mol kg -1 , 0.1~3mol kg -1 , 0.1~3mol kg -1 .
5. The water-in-salt redox hydrogel electrolyte according to claim 1, characterized in that: The concentration of potassium bromide in the electrolyte is 0.5 to 1 mol kg -1 .
6. A method for preparing the water-in-salt redox hydrogel electrolyte according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: Weigh a certain amount of zinc chloride and dissolve it in water to obtain a zinc chloride concentration of 7.5-10 mol kg -1 of a saline-water solution; Step 2, weighing a certain amount of redox active material and dissolving it in a salt-in-water solution to prepare a redox salt-in-water solution; The redox active substance is ammonium ferrous sulfate, potassium bromide, zinc bromide, zinc iodide or potassium iodide, and the concentration of the redox active substance in the prepared redox salt-water solution is 0.05-0.3 mol kg -1 , 0.1~3mol kg -1 , 0.1~3mol kg -1 , 0.1~3mol kg -1 or 0.1~3mol kg -1 ; Step 3, adding the polymer matrix to the redox salt solution in a mass ratio of (1-3) to the salt solute of (5-15), heating in a water bath with stirring until the polymer matrix is completely dissolved; Step 4: Cool naturally to room temperature and place to obtain a water-in-salt redox hydrogel electrolyte.
7. The method for preparing the water-in-salt redox hydrogel electrolyte according to claim 6, characterized in that: In step 3, the water bath heating temperature is 60 to 100° C., and the stirring time is 1 to 3 hours.
8. A method for preparing the water-in-salt redox hydrogel electrolyte according to any one of claims 1 to 3 or 5, characterized in that: The steps include: Step 1: Weigh a certain amount of zinc chloride and dissolve it in water to obtain a zinc chloride concentration of 7.5-10 mol kg -1 of a saline-water solution; Step 2: Weigh a certain amount of potassium bromide and dissolve it in the salt-water solution to obtain a potassium bromide concentration of 0.5 to 1 mol kg -1 A redox salt-containing aqueous solution; Step 3, adding 0.2 to 1 parts by weight of polyvinyl alcohol to the redox salt solution, heating in a water bath and stirring until the polymer matrix is completely dissolved, taking out and cooling to room temperature; Step 4: add 1 to 7 parts by weight of acrylamide, 0.01 to 0.1 parts by weight of ammonium persulfate and 0.003 to 0.01 parts by weight of N,N-methylenebisacrylamide to the solution obtained in step 3 in sequence, dissolve completely, heat, and take out after polymerization reaction to obtain a water-in-salt redox hydrogel electrolyte.
9. The method for preparing the water-in-salt redox hydrogel electrolyte according to claim 8, characterized in that: In step 3, the heating temperature of the hot water bath is 60-100° C., and the stirring time is 1-3 hours; in step 4, the solution is placed in an oven at 50-100° C. for polymerization for 1-5 hours.
10. Use of the water-in-salt redox hydrogel electrolyte according to any one of claims 1 to 5 in preparing a flexible supercapacitor.